2021
DOI: 10.1038/s41540-020-00162-6
|View full text |Cite
|
Sign up to set email alerts
|

Sparsely-connected autoencoder (SCA) for single cell RNAseq data mining

Abstract: Single-cell RNA sequencing (scRNAseq) is an essential tool to investigate cellular heterogeneity. Thus, it would be of great interest being able to disclose biological information belonging to cell subpopulations, which can be defined by clustering analysis of scRNAseq data. In this manuscript, we report a tool that we developed for the functional mining of single cell clusters based on Sparsely-Connected Autoencoder (SCA). This tool allows uncovering hidden features associated with scRNAseq data. We implement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…For each disease, we extracted the largest connected component from the subnetwork composed of genes that were modulated in that specific disease condition and verified whether these genes presented a statistically significant ability to generate a disease module. For subsequent analyses, we selected only the diseases that satisfied this module hypothesis, in accordance with the organizing principles of network medicine [3] , [9] , [39] . Notably, we found that for all diseases analyzed (with the exception of ankylosing spondylitis and chronic spontaneous urticaria), the deregulated genes formed statistically significant modules ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each disease, we extracted the largest connected component from the subnetwork composed of genes that were modulated in that specific disease condition and verified whether these genes presented a statistically significant ability to generate a disease module. For subsequent analyses, we selected only the diseases that satisfied this module hypothesis, in accordance with the organizing principles of network medicine [3] , [9] , [39] . Notably, we found that for all diseases analyzed (with the exception of ankylosing spondylitis and chronic spontaneous urticaria), the deregulated genes formed statistically significant modules ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even though the cause-effect relationship cannot be directly inferred by expression data, it is reasonable to assume that disease co-modulated genes are functionally coordinated in response to an external stimulus, implying that they might be part of the same pathways or biological functions, and may influence each other or be influenced by the same underlying mechanism(s). Inspired by the organizing principles of the network medicine paradigm, we evaluated whether disease deregulated genes had the propensity to aggregate in local disease-specific neighborhoods of the human interactome, thus being functionally-related genes displaying a statistically significant tendency to form dense disease modules [3] , [9] , [39] . The accurate identification and localization of these disease modules represents the first step toward a systematic understanding of molecular-level pathological mechanisms, together with the prediction of novel disease-disease relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…159 microarray datasets were integrated with 20 proteomic datasets to define the gene activity profiles (matrices) of the five phenotypes. The profiles and the generic human metabolic model Recon 2.2.05 [ 23 ] were used to build the constraint-based models by the GIMME method in the COBRA toolbox [ 48 ]. In summary, the Th0 model contains 4234 metabolic fluxes and 2452 metabolites; Th1, 4160 and 2377; Th2, 4674 and 2623; Th17, 5223, and 2833; and Treg, 3854 and 2178.…”
Section: Methodsmentioning
confidence: 99%
“…Another example of the use of VAE in single cell data is scVAE [ 11 ] and SCA [ 66 ], which are employed for classification/clustering tasks. scVAE uses different types of VAE with either a Gaussian or a Gaussian-mixture latent variable prior.…”
Section: Ae Applications In Biological and Medical Contexts Beyond Rdmentioning
confidence: 99%